The Effectiveness of Intense Pulsed Light (Home Use) Device in Facial Hair Reduction - Dawood, Russul A.; Al-Battat, Rzan Abdulhsan; Funjan, Mawada M (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Intense pulsed light (IPL) devices produce polychromatic incoherent high-intensity pulsed light with a specified wavelength spectrum, fluence, and pulse duration through the use of flashlamps and bandpass filters. Similar to lasers, IPL devices operate on the selective photothermolysis principle, with melanin acting as the chromophore. Despite this similarity, they are constructed differently and produce different amounts of light Aim of the study: To investigate the efficacy of IPL home-use device in hair reduction technique for women with unwanted facial hair. Subjects and methods: The study was conducted in Baghdad on forty-five female subjects with Fitzpatrick skin phototype (II to IV) and black, brown hair in a period of eight months with five sessions. The treatment area (1 of chin) photographs and the density of hair (hair count) after each session were compared to the pretreatment. Results: After five sessions a percentage average of hair reduction reached 70.9% (P-value ≤0.01) from the pretreatment density of hairs. Also, the physician’s GAIS(global esthetic improvement scale) score was used in order to evaluate hair reduction. After five sessions, it was found that 40% of the subjects had excellent response, 56.6% had good responses and 3.33% had average responses (p-value ≤0.01) Conclusion: The current study shows that the IPL technique used for hair reduction is effective and safe to use for the subject’s Fitzpatrick skin phototypes (II to IV) facial hair.